(3GdCPcGQs - (3GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjGA, eMj GdOjf, jMj Hf TQa Hf eQj, J (B676(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO dnqdg GdhGMO GdbnqgGQ, GdYRjR GdZnqaGQ, ebpqOQ GdCbOGQ, eUpqQa GdCehQ oecpqhQ Gddjd Ydi GdfgGQ, JHUQnI doChdj GdbdhH hGdCHUGQ, GdPj CjbX ef Ndbgs
(3BNQgG (B:s
(3QhjfG aj (B" (3UMjM GdHNGQj (B" (3Yf CfS QVj Gddg Yfg Yf GdfHj Udi Gddg Ydjg hSde(B: " (3Cfg cGf EPG Jcde HcdeI CYGOgG KdGKG MJi ojage Yfg, hEPG CJi Ydi bhe aSnqde Ydjge Snqdne Ydjge KdGKkG (B" (3bdJ(B: (3hgPG GdMOjK eMehld Ydi eG EPG cGf GdLeoY cKjQkG, hSjCJj HjGf gPg GdeSCdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 /149s
(3eYLe GdeDdajf (B4 / 98s
(3cTa GdXfhf (B1/ 688s
(3TPQGJ GdPgH (B5/ 354s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs